The Effect of Metformin on Coagulation Profiles in Type II Diabetes Mellitus: A Tertiary Care Hospital of Nepal - Maharjan, Sabindra; Bhatt, Mahendra; Lamichhane, Anit; Jha, Bipin Kumar; Twayana, Saru; Nepal, Bipin (Grande Medical Journal, 2025)
Background: Type II Diabetes Mellitus (T2DM) is associated with a prothrombotic state due to altered coagulation and fibrinolysis. Metformin, the first-line treatment for T2DM, may influence coagulation parameters, but this effect is underexplored in the Nepalese population. The purpose of this study was to assess how metformin affected the levels of D-dimer, prothrombin time (PT), and activated partial thromboplastin time (APTT) in patients with type 2 diabetes. Method: Glycemic control and metformin use were used to group 120 T2DM patients and 120 healthy controls in a cross-sectional study. PT, APTT, D-dimer, and platelet count tests were performed on blood samples and the effects of raising glucose concentrations with and without metformin were evaluated using an in vitro model. Result: PT, APTT, and D-dimer levels were significantly higher in T2DM patients (p<0.05), with more noticeable changes in those with poorly controlled diabetes. Patients receiving metformin showed some degree of normalization which indicate that Metformin partially reversed the effects of high glucose on coagulation markers in vitro. Conclusion: Metformin may enhance coagulation profiles, which would support its use in conjunction with glycemic control and lower the risk of thrombosis.